Consumption of eggs as a protein source by practitioners and non-practitioners of physical activity in Maringá – PR (Research, Society and Development, 2022)
Egg consumption has been increasing over time, this may be related to its cost-effectiveness, as it is considered a low-cost protein and has a rich composition in nutrients. The objective of this work was to know the profile of practitioners and non-practitioners of physical activities in the city of Maringá-PR, directly correlating with the consumption of eggs as the main source of protein. The study was carried out with residents of the city of Maringá-PR, 343 people were interviewed between April (2021) and June (2021). The semi-structured forms were applied through the Google Forms digital platform, due to the pandemic caused by Covid-19, and were disseminated on digital media such as Facebook, Instagram, WhatsApp and via email. The main sport of the interviewees was walking/running 20.00(%). The main source of protein consumed by practitioners and non-practitioners of physical activity in the city of Maringá-PR was beef (18.30%) and only for 3.83% of the participants the main source of protein was eggs. Of those interviewed, 99.15% believe that egg consumption is healthy and 88.09% do not correlate this consumption with diseases.